Sulfur(VI) Fluoride Exchange (SuFEx)-Mediated Synthesis of the Chitosan-PEG Conjugate and Its Supramolecular Hydrogels for Protein Delivery - Jang, Kyoung-Je (Nanomaterials (Basel), 2021)
Supramolecular hydrogels are considered promising drug carriers in the tissue engineering field due to their versatile nature. Chitosan hydrogels without chemical cross-linkers have low cytotoxicity and good delivery capacity; however, they have lower mechanical properties for injectable hydrogel usage. In this study, we developed novel chitosan derivatives via click chemistry for fabricating supramolecular hydrogels with higher mechanical strength under mild conditions. The chitosan derivative was successfully synthesized by a sulfur fluoride exchange reaction, and the synthesized chitosan-mPEG/Pluronic-F127 (CS-mPEG/F127) interacted with α-cyclodextrin (α-CD) to form a supramolecular hydrogel via a host-guest reaction. The gelation dynamics, hydrogel properties, and bovine serum albumin (BSA) release could be modulated by the concentration ratio of chitosan-mPEG and F127. This supramolecular hydrogel is a promising protein releasing carrier candidate for long term regeneration therapy.